Diagnostic Value and Application of Prenatal MRI and Ultrasound in Fetal Cleft Lip and Palate. (18th May 2022) - Yan, Xin; Xing, Guojing; Wang, Xin; Li, Jun; Sun, Qiuhong; Shang, Xiaojie
Abstract : Objective . The purpose was to explore the diagnostic value and application of prenatal magnetic resonance imaging (MRI) and ultrasound (US) in fetal cleft lip and palate. Methods . From January 2018 to December 2019, 39 pregnant women without normal fetal maxillofacial structure or with fetal maxillofacial deformity under US examination in our hospital were selected as the study subjects. Not knowing the clinical data of the pregnant women, MRI and US physicians performed diagnostic analysis on the MRI or US images of all the study subjects and analyzed the results of prenatal MRI and US diagnosis and postpartum follow-up to compare the diagnostic efficacy and confidence of MRI and US. Results . The follow-up found that there were 20 cases of cleft lip, 15 cases of cheilopalatognathus, 3 cases of cleft palate, and 1 case of unilateral cleft lip with alveolar cleft, with a total of 39 cases having cleft lip and palate deformity. MRI and US had the same efficacy in the diagnosis of cleft lip. As for cleft palates, the diagnostic accuracy of MRI (94.87%) was significantly better than that of US (48.72%, P  < 0.001). The diagnostic confidence of fetal cleft lip and palate by MRI (89.73%) was significantly better than that of US (43.59%, P  < 0.001). The AUC of US (0.597) was significantly less than that of MRI (0.940), indicating that the diagnostic accuracy of US was not as good as that of MRI ( P  < 0.05). The sensitivity and 1 − specificity of MRI were significantly higher than those of US. Conclusion . MRI is more accurate than US in the diagnosis of fetal cleft lip and palate, and MRI can be the preferred method for prenatal detection of cleft lip and palate, thus providing more accurate opinions and information for perinatal pregnant women.